PENGARUH SUHU YANG BERBEDA TERHADAP DAYA TETAS TELUR DAN KELANGSUNGAN HIDUP LARVA IKAN LELE SANGKURIANG (Clarias gariepinus) - Suara Ningsih, Aisyah; Zulkhasyni; Martudi, Suharun; Tri Utami, Risnita; Syukhriani, Silvy (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
The aim of this research is to determine the best temperature for egg hatching and survival of sangkuriang catfish (Clarias gariepinus) larvae. This research was carried out for 30 days, 29 May – 29 June 2024, located at the Laboratory of the Faculty of Agriculture, Prof. University. Dr. Hazairin SH. Bengkulu Jl. A. Yani Bengkulu City District. Segara Bay. The design used in this research was a Completely Randomized Design (CRD) which consisted of four treatments and six replications, each treatment as follows: P1 (temperature 29ºC), P2 (temperature 30ºC), P3 (temperature 31ºC) and P4 (temperature 32ºC). The fecundity of Sangkuriang catfish obtained was 90,000 eggs. Water temperature has a very significant effect on hatching time, egg hatchability and survival of sangkuriang catfish (Clarias gariepinus) larvae. Hatching time The best temperature is 31ºC - 32ºC, while the best hatchability and survival of sangkuriang catfish larvae is at 30ºC where hatchability is 84.33% and survival is 82%.